Tenacious of Life : The Quadruped Essays of John James Audubon and John Bachman - Audubon, John James, 1785-1851; Bachman, John, 1790-1874 (Book collections on Project MUSE., 2021)
"Daniel Patterson and Eric Russell present a groundbreaking case for considering John James Audubon's quadruped essays as worthy of literary analysis, as well as redefining the role of John Bachman, the perpetually overlooked coauthor of the essays"--